Ethnoscience Studies in Songket Sasak Cloth Motifs: Prospective Science Teacher Perceptions - Agus Muliadi; Suhirman Suhirman; M. Khairul Wazni; M. Yamin; Yusran Khery (Postgraduate, University of Mataram, 2022)
The aims of this study were to explore the perceptions of prospective science teachers towards ethnoscience studies in the songket cloth motif of the sasak tribe. This exploratory research conducted in three education study programs namely Biology, Chemistry, and Physics Education with 53 prospective science teachers involved as research subject. Closed questionnaire with likert scale and expertly validated applied for data collection. The data were analyzed by quantitative descriptive statistics, Anova test and t-test inferential statistics. The results showed that (1) perception of prospective science teachers has an average score in the